2019
DOI: 10.18196/jesp.20.1.5016
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Inflation Rate in Indonesia

Abstract: This study aims to analyze the influence of some independent variables which are believed to have an impact on inflation in Indonesia. Also, as one of the variables that are observed by the Central Bank of Indonesia as a variable that could influence inflation stability in Indonesia based on its volatility. Those independent variables are divided in four categories namely money supply, exchange rate, BI rate as the interest rate, and gross domestic product. The data were obtained from the Indonesian Economic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 4 publications
(4 reference statements)
0
3
0
1
Order By: Relevance
“…When the inflation rate increases, Bank Indonesia will respond by raising the BI Rate to put the brakes on fast-moving economic activity to reduce inflationary pressures (Bank Indonesia, 2013). This finding is different from the results conducted by Kalalo (2016), Utama et al, (2017) and Setiartiti & Hapsari (2019). Where they found that the BI Rate variable has a positive influence on the inflation rate.…”
Section: Discussioncontrasting
confidence: 73%
“…When the inflation rate increases, Bank Indonesia will respond by raising the BI Rate to put the brakes on fast-moving economic activity to reduce inflationary pressures (Bank Indonesia, 2013). This finding is different from the results conducted by Kalalo (2016), Utama et al, (2017) and Setiartiti & Hapsari (2019). Where they found that the BI Rate variable has a positive influence on the inflation rate.…”
Section: Discussioncontrasting
confidence: 73%
“…So, the bank will not experience a deficit in channeling funds or financing to the public. Indonesian central bank must maintain inflation rate in the safety level for financial industry by following determined inflation target through appropriate monetary policies (Setiartiti & Hapsari, 2019;Fakhrunnas, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Menurut Setiartiti & Hapsari (2019) dalam penelitiannya di Indonesia menyatakan bahwa pengaruh produk domestik bruto terhadap inflasi menunjukkan bahwa terdapat hubungan yang negatif antara PDB dan Inflasi. Peningkatan produk domestik bruto atau total output akan menurunkan inflasi.…”
Section: Pertumbuhan Ekonomiunclassified